One-Step Non-Contact Additive LIFT Printing of Silver Interconnectors for Flexible Printed Circuits - Alena Nastulyavichus; Sergey Kudryashov; Svetlana Shelygina; Nikita Smirnov; Petr Pakholchuk; Irina Saraeva; Dmitry Zayarny; Evgenia Ulturgasheva; Dmitry Khmelenin; Olga Emelyanova; Victoria Pryakhina; Nikolay Pokryshkin; et al. (Photonics, 2024)
The single-pass one-step method for printing conductive silver tracks on a glass surface, using the laser-induced forward transfer (LIFT) technique, was proposed, providing a unique opportunity for high-throughput printing of surface micro- and nanostructures with high electrical conductivity and positioning accuracy. This method was developed via our multi-parametric research, resulting in the selection of the optimal material, laser irradiation, and transfer conditions. Optical, scanning and transmission electron, and atomic force microscopy methods, as well as X-ray diffraction, were used to characterize the surface structure and phase state of the printed structures, while energy-dispersive X-ray and X-ray photoelectron microscopy were employed for their chemical microanalysis. Depending on the laser irradiation parameters, the specific electrical conductivity of the printed tracks varied from 0.18 to 83 kS/cm, approaching that of donor magnetron-sputtered films. This single-pass one-step method significantly facilitates fast, large-scale, on-demand local laser printing of metallic (sub)microcomponents of microelectronic devices.